Modelos para produção de hidrogênio a partir de duas rotas: reator a membrana e eletrolisadores PEM - uma introdução - Silva, Isaac Enos da (2024)
Hydrogen stands out as a promising energy vector due to its versatility and abundance, especially in a scenario of increasing demand for sustainable energy sources. Membrane reactors, innovative devices that use membranes to separate products and reactants during chemical reactions, have proven efficient in improving process conversion. The production of green hydrogen through electrolysis, using PEM electrolyzers, emerges as a clean and relevant solution for reducing greenhouse gas emissions. This work focuses on analyzing hydrogen production through membrane reactors and PEM electrolyzers, employing the Python programming language and a chemical process simulator. The modeling and simulation considered operational variables such as temperature, pressure, and reactant flow rates, with the model being validated based on experimental data available in the literature. The results indicated that, in case study 1, methane (CH₄) conversion in a membrane reactor varied with temperature, pressure, and membrane thickness. At 350°C, conversion was low, not exceeding 3.5%. At 500°C, it increased to up to 60% at 30 bar. At 750°C, conversion reached nearly 100%, with the impact of pressure becoming less relevant. Thin membranes (6 µm) favored higher conversion under less demanding conditions, while thicker membranes (30 µm) resulted in lower efficiency. These results highlight the importance of optimizing operational conditions. In case study 2, membrane reactors showed high efficiency in methane conversion, especially under high pressures. In case study 3, the production of hydrogen using PEM electrolyzers powered by solar energy was analyzed. The system operated for 13 hours, with a production rate of 1.5 micrograms per second and a pressure of 890 kPa (8.9 bar). The purity of the hydrogen produced was high, with molar fractions of hydrogen (z[H₂], y[H₂], x[H₂]) equal to 1, with no presence of oxygen or water vapor. These results, consistent with the existing literature, reinforce the effectiveness of membrane reactors and PEM electrolyzers, highlighting the importance of optimizing operational conditions to maximize both natural gas conversion and sustainable energy production.